2010
DOI: 10.1108/17410381011063987
|View full text |Cite
|
Sign up to set email alerts
|

Management directed kaizen: Toyota's Jishuken process for management development

Abstract: Purpose -The purpose of this paper is to analyze Toyota's management directed kaizen activities named Jishuken. Currently, there are many variations in understanding how Toyota develops its managers to support daily kaizen, especially when Toyota managers have different levels of understanding of Toyota production system (TPS) and skills essential in applying TPS. Design/methodology/approach -This paper will study Toyota's Jishuken process in the context of strengthening TPS and analyze both the technical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 6 publications
1
36
0
5
Order By: Relevance
“…The primary difference between the so-called quality control (QC) circles and jishuken is that the former are focused on kaizen within single divisions, while the latter involve multiple corporations and divisions. The automakers assume a leadership role in jishuken; however, it is noteworthy that suppliers express opinions and ideas in the communication process (Marksberry et al, 2010). Study groups similar to jishuken can be found associated with automakers other than Toyota; however, Toyota's suppliers are known to be more committed compared to those of other automakers (Manabe, 2004).…”
Section: Information Gatheringmentioning
confidence: 97%
“…The primary difference between the so-called quality control (QC) circles and jishuken is that the former are focused on kaizen within single divisions, while the latter involve multiple corporations and divisions. The automakers assume a leadership role in jishuken; however, it is noteworthy that suppliers express opinions and ideas in the communication process (Marksberry et al, 2010). Study groups similar to jishuken can be found associated with automakers other than Toyota; however, Toyota's suppliers are known to be more committed compared to those of other automakers (Manabe, 2004).…”
Section: Information Gatheringmentioning
confidence: 97%
“…In fact, available performance indicators have a critical role on lean practices. Continuous improvement initiatives often begin with information from key performance indicators (Marksberry et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bhasin e Burcher (2006) acrescentam a necessidade de fomentar os princípios lean também por meio da cadeia de valor. Conforme Marksberry et al (2010), é importante entender porque a técnica existe, para, assim, definir a cultura organizacional necessária. Yamamoto e Bellgran (2010) sugerem que deve ser criado um ambiente que fomente a necessidade das melhorias decorrentes da implantação do sistema lean, para, desse modo, transpor barreiras à implantação da metodologia.…”
Section: Cultura Organizacionalunclassified